EXERCÍCIOS DE RESPOSTA A INCIDENTES DE POLUIÇÃO POR ÓLEO: UMA PROPOSTA DE MODELO DE AVALIAÇÃO. - Pinto, Renato Spíndola de Miranda (2005)
Nowadays companies strongly invest in the establishment of parameters that reflect their environmental concern, in a way that allow a sustainable coexistence and guarantee their acceptance and maintenance in the economical-social context. The companies responsibility is beyond the preventive structure for incidents, demanding appropriate response plan to minimize their consequences. For a correct response capacity assessment, it is necessary to attempt the execution and evaluation of response exercises to pollution incidents. This dissertation intends to show the effective vision of the PETROBRAS, through the characterization of the petroleum segment s response process increase, from the beginning to the actual panorama in the Brazilian south and southeast marine petroleum basins, relative to the realization of response exercises to prevent oil pollution incidents, culminating with an improvement proposal for this process evaluation. The model proposal is made through the adjustment of the Response Scorecard for Area Emergency Plans, that is based in the concepts of Incidents Command System (SCI) and Balanced Scorecard (BSC), resulting in Response Scorecard for Exercises of Oil Pollution Incidents Answer (RSC) and in the definition of the requirements that should be observed in the evaluation of each point of interest. The proposed model intends to offer a tool that increases the range of the exercises evaluation, addresses it to the areas of interest for the answer to oil pollution incidents, improves the quality of the evaluation and stimulates the decrease of the subjectivity in the evaluators' perception and the increase of the number of improvement indications on each evaluation. Finally, through the comparison of the proposed model with the systematic of evaluation in use, it concludes that the adoption of the proposed model will bring significant improvement for the oil pollution incidents answer process.